"Happy accidents": Innovation-driven opportunities and perspectives for development in the knowledge economy - Elias G. Carayannis; David F. J. Campbell; Scheherazade S. Rehman (Journal of Innovation and Entrepreneurship, 2015)
From Development as Democracy to Innovation as Development: Current local, regional, and global economic and financial conditions and trends make the need to trigger, catalyze and accelerate high quantity and quality entrepreneurial initiatives that are based on high quality and quantity innovations. Given the uncertainty and change inherent in the innovation process, management must develop skills and understanding of the process: a method for managing the disruption. Technology changes the way society functions. The dramatic advances in technology over recent decades have collaterally precipitated wide sweeping and profound change to the functioning of almost every form of human exchange, the world over. Income inequality in the US has being growing since the late 1970s, but easy credit and rising asset prices had allowed American households to increase financial leverage to finance consumption. Now an increasing number of academics and intellectuals recognize that the growing income inequality is one of the key aspects behind the financial crash. The first step in understanding how the income re-distribution can lead to innovation and help an economy move from a stagnant state into a new sustainable economic growth path is to understand how long-term trends in rising and falling income inequality affect the market environment that firms must survive in. In the late twentieth and the beginning of the twenty-first century, numerous scholars and practitioners such as Peter Drucker have identified knowledge as a crucial and most important key input and output factor of economic activity. The knowledge-based economy can be characterized as fractal. It is non-linear, unstable, and stochastic. From Development as Democracy to Innovation as Development: and back to from Innovation as Development to Development as Democracy.
Keywords: 650; Democracy; Development; Cyber-Democracy; Cyber-Development; e-Development; Equality; Happy accidents; Innovation; Knowledge economy; Sustainable development; Technology